The first 90 days: proven strategies for getting up to speed faster and smarter proven strategies for getting up to speed faster and smarter / Michael D. Watkins - Watkins, Michael
Since its original release, The First 90 Days has become the bestselling globally acknowledged bible of leadership and career transitions. In this updated and expanded 10th anniversary edition, internationally known leadership transition expert Michael D. Watkins gives you the keys to successfully negotiating your next move--whether you're onboarding into a new company, being promoted internally, or embarking on an international assignment. In The First 90 Days, Watkins outlines proven strategies that will dramatically shorten the time it takes to reach what he calls the "breakeven point" - when your organization needs you as much as you need the job. This new edition includes a substantial new preface by the author on the new definition of a career as a series of transitions; and notes the growing need for effective and repeatable skills for moving through these changes. As well, updated statistics and new tools make this book more reader-friendly and useful than ever. As hundreds of thousands of readers already know, The First 90 Days is a road map for taking charge quickly and effectively during critical career transition periods--whether you are a first-time manager, a mid-career professional on your way up, or a newly minted CEO